All Roads Lead to Risk Preference: A Turnpike Theorem for Conditionally Independent Returns - McCardle, Kevin F.; Winkler, Robert L. (Journal of Financial and Quantitative Analysis, 1989)
Kevin F. McCardle, Robert L. Winkler, All Roads Lead to Risk Preference: A Turnpike Theorem for Conditionally Independent Returns, The Journal of Financial and Quantitative Analysis, Vol. 24, No. 1 (Mar., 1989), pp. 13-28